2017
DOI: 10.22571/actabra1120176
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporium spp: Morfologia, infecções e espécies patogênicas

Abstract: ResumoO gênero Cladosporium spp compreende grande número de fungos dematiáceos com distribuição mundial e que estão entre os fungos de ambiente mais comuns. São frequentemente isolados como contaminantes, no entanto, algumas espécies são patogênicas e toxigênicas para os seres humanos, estando associados a infecções superficiais da pele e dos tecidos moles e incluem sepse disseminada com elevada mortalidade. Cladoporium spp são aero-alérgenos e causam graves doenças alérgicas do trato respiratório, bem como le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
6
0
4
Order By: Relevance
“…They are considered among the fungi with the highest concentration in the atmosphere, mainly in tropical and sub-tropical climate regions (Zoppas et al, 2011). Menezes et al (2017) depicted the fungi of this genus as endowed with great adaptive capacity, capacity for contamination and colonization of different environments, as it was possible to verify in this study, where this genus was isolated from the integument of several species of anteater studied. As observed by means of other authors, in this research, the macro morphological evaluation of Cladosporium spp.…”
Section: Figurementioning
confidence: 57%
See 1 more Smart Citation
“…They are considered among the fungi with the highest concentration in the atmosphere, mainly in tropical and sub-tropical climate regions (Zoppas et al, 2011). Menezes et al (2017) depicted the fungi of this genus as endowed with great adaptive capacity, capacity for contamination and colonization of different environments, as it was possible to verify in this study, where this genus was isolated from the integument of several species of anteater studied. As observed by means of other authors, in this research, the macro morphological evaluation of Cladosporium spp.…”
Section: Figurementioning
confidence: 57%
“…However, there are already references to the pathogenic power of these fungi. Menezes et al (2017) reported in their research that the genus Cladosporium spp. it can cause from epithelial lesions, such as keratitis, with organ involvement, to the development of brain abscesses (Oliveira et al, 2001).…”
Section: Figurementioning
confidence: 99%
“…Among microorganisms identified in this study, it is considered that Aspergillus, Penicillium and Fusarium are potential producers of mycotoxins, which can cause serious neurogenic, teratogenic, carcinogenic and immunosuppressive problems (Calvet et al, 2012;Sun et al, 2014;Kim et al, 2020). The Cladosporium, in turn, is generally considered a food contaminant, but some species are pathogenic to humans, related to skin infections, rhinosinusitis, brain abscess and septicemia (Menezes et al, 2017;Garcia et al, 2018;Ahn et al, 2019;Batra et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…In the present work, these results were not observed with clove essential oil. According to Menezes et al (2017) the genus Cladosporium sp. comprises a large number of fungi with worldwide distribution and which are among the most common environmental fungi.…”
Section: Discussionmentioning
confidence: 99%